Port Efficiency and Regional Development - Eduardo Haddad; Geoffrey Hewings; Raul Dos Santos (European Regional Science Association (ERSA), 2006)
This paper attempts to elucidate one of the mechanisms that link trade barriers, in the form of port costs, and subsequent growth and regional inequality. Not only inland costs can be perceived as a further barrier to link trade liberalization and growth (Haddad and Perobelli, 2005), but also port costs. Unlike highway link, congestion at port may have severe impacts spread over space and time whereas highway link congestion may be resolved within several hours. Since port is part of the transportation network, any congestion/disruption is likely to ripple throughout the hinterland. In this sense, it is important to model properly the role nodal congestion plays in a context of spatial models and international trade. Thus, we have developed a spatial CGE model integrated to a transport network system in order to simulate the impacts of increases in port efficiency in a context of trade liberalization. The role of ports of entry and ports of exit are explicitly considered in order to grasp the holistic picture in an integrated interregional system.
Keywords: 330